The Parallels of White Supremacy Discourse in Bitita’s Diary and Racism in a Racial Democracy - Jerry Scruggs (Vernacular: New Connections in Language, Literature, & Culture, 2018)
This paper explores the workings of white supremacy within a rural Brazilian context. France Winddance Twine’s Racism in a Racial Democracy serves as an ideological basis for this analysis of Carolina Maria de Jesus’s Bitita’s Diary, and shows how systemic and rampant white supremacy has weighed on the psyche of Afro-Brazilians and how it persists to the present day.
Keywords: Bitita; Carolina de Jesus; racial democracy; whitening; social ascension; Afro-Brazilianess